2022
DOI: 10.14639/0392-100x-n1803
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative respiratory complications in children with obstructive sleep apnoea syndrome

Abstract: SUMMARY Objective We aimed to prospectively assess the effect of comorbidities on the occurrence of postoperative respiratory complications (PoRCs) after adenotonsillectomy in children with obstructive sleep apnoea syndrome (OSA) and whether otherwise healthy children need a higher level of postoperative monitoring. Methods 577 children who had OSA and underwent adenotonsillectomy were enrolled. The effects of demographics, comorbidities and OSA on PoRCs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…It has been suggested that comorbidities, such as obesity, age, prematurity, and respiratory disorders (among others), are stronger predictors of postoperative complications than OSAS severity. 17 Our study on preoperative cardiopulmonary abnormalities also indicates that existence of cardiopulmonary comorbidities, more so than OSAS severity, is a better predictor of abnormal echocardiogram and chest x-ray results. 6 This is in contrast to research from Demir and colleagues which showed no significant increase in postoperative complications following adenotonsillectomy in patients with comorbidities.…”
Section: Discussionsupporting
confidence: 54%
“…It has been suggested that comorbidities, such as obesity, age, prematurity, and respiratory disorders (among others), are stronger predictors of postoperative complications than OSAS severity. 17 Our study on preoperative cardiopulmonary abnormalities also indicates that existence of cardiopulmonary comorbidities, more so than OSAS severity, is a better predictor of abnormal echocardiogram and chest x-ray results. 6 This is in contrast to research from Demir and colleagues which showed no significant increase in postoperative complications following adenotonsillectomy in patients with comorbidities.…”
Section: Discussionsupporting
confidence: 54%
“…8 A prospective study published by Benedek et al in 2022 showed that more than 50% of children with comorbidities suffered from respiratory complications post-adenotonsillectomy, and suggested that all paediatric OSAS patients with comorbidities should be monitored in PACU or PICU for at least 1 night after adenotonsillectomy, irrespective of severity of OSAS. 9 In our c���, th� child i� of 3 y��r� of �g� �ithout �igni�c�nt comorbidity during adenoidectomy, with worsening OSAS as indicated by an increase in the number of clusters of desaturation from 2 to 3, with SPO 2 reaching as low as 54% from 78%, 1 year apart.…”
Section: Resultsmentioning
confidence: 63%
“…The management of childhood obstructive sleep apnea syndrome (OSAS) depends on the severity of the disease, the presence of comorbidities, and the child's age. The American Pediatric Academy recommends a multidisciplinary approach involving a pediatrician, a sleep specialist, and an otolaryngologist to provide comprehensive care for children with OSAS [4,15].…”
Section: Introductionmentioning
confidence: 99%